2016
DOI: 10.1002/adma.201601007
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Electrodes for Flexible Electronics by Swelling Controlled Cracking

Abstract: Nanogap electrodes are realized using pre-patterned electrodes and a swelling controlled cracking method. Parallel fabrication of nanogap electrodes on flexible substrates can be achieved using this method. This swelling-controlled cracking method is promising for fabricating high-performance flexible electronics. UV photodetectors with ZnO nanoparticle-bridged nanogap electrodes exhibit high responsivity and external quantum efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…Fabrication of coplanar asymmetric tip‐to‐edge metal‐based nanostructure with sub‐10 nm air channel and tip‐to‐edge height difference is beyond the ability of conventional semiconductor technologies and the existing nanogap fabricating technologies. [ 48 ] Currently emerging nanogap fabrication routes including typical breaking‐/cracking‐based methods [ 49–53 ] are limited to fabricating symmetric nanogaps with restricted materials. Recently developed adhesion lithography [ 38–44 ] is generally used to produce coplanar material‐asymmetric nanogaps in geometrically symmetric side‐to‐side form, suffering from restricted materials and larger than 10 nm gap spacing.…”
Section: Resultsmentioning
confidence: 99%
“…Fabrication of coplanar asymmetric tip‐to‐edge metal‐based nanostructure with sub‐10 nm air channel and tip‐to‐edge height difference is beyond the ability of conventional semiconductor technologies and the existing nanogap fabricating technologies. [ 48 ] Currently emerging nanogap fabrication routes including typical breaking‐/cracking‐based methods [ 49–53 ] are limited to fabricating symmetric nanogaps with restricted materials. Recently developed adhesion lithography [ 38–44 ] is generally used to produce coplanar material‐asymmetric nanogaps in geometrically symmetric side‐to‐side form, suffering from restricted materials and larger than 10 nm gap spacing.…”
Section: Resultsmentioning
confidence: 99%
“…However, relatively low yields (≈7%) and difficulties in controlling the morphology of the nanogap interfaces remain significant problems. In addition to strain‐induced cracking methods, there are some preliminary reports describing the use of swelling controlled cracking, [ 108 ] intergranular fracturing, [ 109 ] and optical breakdown [ 110 ] which, although relatively unstudied, may have significant potential for array‐based fabrication.…”
Section: Alternative and Emerging Approachesmentioning
confidence: 99%
“…However, close investigation on cracking phenomena and its possible applications have demonstrated cracks as useful features for device fabrication, [22][23][24][25] for growth of nanowires or to form nanochannels, 26,27 as a tool for controlled patterning during thin lm deposition 28 and as microuidic channels. 29,30 There are some published reports on crack based lithography. [31][32][33][34] Dubois et al have shown crack junctions dening nanogap in titanium nitride (TiN).…”
Section: Introductionmentioning
confidence: 99%